Mix proportioning of M80 grade Self-Compacting Concrete based on Nan Su Mix design method principles - Shrihari, S; V Seshagiri Rao, M; Srinivasa Reddy, V; Sai, Venkat (International Journal of Engineering and Technology, 2018)
The quest for the development of high strength and high performance concretes has increased considerably in recent times because of the demands from the construction industry. High-performance concretes can be produced at lower water/powder ratios by incorporating these supplementary materials. Fly ash addition proves most economical among these choices, even though addition of fly ash may lead to slower concrete hardening. However, when high strength is desired, use of silica fume is more useful. This paper proposes a mix proportions for M80 grade Self-compacting concrete (SCC) based on Nan Su mix design principles. First, the amount of aggregates required is determined, and the paste of binders is then filled into the voids of aggregates to ensure that the concrete thus obtained has flowability, self-compacting ability and other desired SCC properties. The amount of aggregates, binders and mixing water, as well as type and dosage of superplasticizer (SP) to be used are the major factors influencing the properties of SCC. Slump flow, V-funnel, L-flow, U-box and compressive strength tests were carried out to examine the performance of SCC, and the results indicate that the Nan Su method could produce successfully SCC of high strength. Based on Nan Su mix design method, material quantities such as powder content ( Cement + Pozzolan ), fine aggregate, coarse aggregate, water and dosages of SP and VMA, required for 1 cu.m, are evaluated for High strength grade (M80) of Self Compacting Concrete (SCC) are estimated. Final quantities, of M80 grade SCC mix, is assumed after several trial mixes on material quantities computed using Nan Su mix design method subjected to satisfaction of EFNARC flow properties.